NUPR1 protects liver from lipotoxic injury by improving the endoplasmic reticulum stress response. Issue 3 (10th February 2021) - Teresa Borrello, Maria; Rita Emma, Maria; Listi, Angela; Rubis, Marion; Coslet, Sergiu; Augello, Giuseppa; Cusimano, Antonella; Cabibi, Daniela; Porcasi, Rossana; Giannitrapani, Lydia; Soresi, Maurizio; Pantuso, Gianni; et al.
Abstract: Non‐alcoholic fatty liver (NAFL) and related syndromes affect one‐third of the adult population in industrialized and developing countries. Lifestyle and caloric oversupply are the main causes of such array of disorders, but the molecular mechanisms underlying their etiology remain elusive. Nuclear Protein 1 (NUPR1) expression increases upon cell injury in all organs including liver. Recently, we reported NUPR1 actively participates in the activation of the Unfolded Protein Response (UPR). The UPR typically maintains protein homeostasis, but downstream mediators of the pathway regulate metabolic functions including lipid metabolism. As increases in UPR and NUPR1 in obesity and liver disease have been well documented, the goal of this study was to investigate the roles of NUPR1 in this context. To establish whether NUPR1 is involved in these liver conditions we used patient‐derived liver biopsies and in vitro and in vivo NUPR1 loss of functions models. First, we analyzed NUPR1 expression in a cohort of morbidly obese patients (MOPs), with simple fatty liver (NAFL) or more severe steatohepatitis (NASH). Next, we explored the metabolic roles of NUPR1 in wild‐type ( Nupr1 +/+ ) or Nupr1 knockout mice ( Nupr1 −/− ) fed with a high‐fat diet (HFD) for 15 weeks. Immunohistochemical and mRNA analysis revealed NUPR1 expression is inversely correlated to hepatic steatosis progression. Mechanistically, we found NUPR1 participates in the activation of PPAR‐α signaling via UPR. As PPAR‐α signaling is controlled by UPR, collectively, these findings suggest a novel function for NUPR1 in protecting liver from metabolic distress by controlling lipid homeostasis, possibly through the UPR.